(untitled) (Journal of Surgical Sciences, 2026)
Introduction: After laparoscopic low anterior resection surgery, diversion ileostomy is a conceded procedure. However, reversal time of diversion ileostomy is still arbitrary. Ileostomy affects the patients’ Quality of Life and demands reversal but short gap between two surgeries is very crucial particularly for elderly patients. Methods: This is a retrospective study. Data of eighteen patients, who underwent anterior resection for rectal tumors and diversion ileostomy were collected. The study was conducted at Popular Medical college Hospital in Dhaka, Bangladesh between March 2018 and January 2022. The patients were divided in Early Closure and Late Closure groups. Results: Early closure (mean interval time was 16.5 days) of covering ileostomy was undertaken among 9 patients. Among them. three developed surgical site infection following ileostomy reversal and no other major complication was experienced by any of them. On the other hand, 8 patients were destined to undergo ileostomy closure after 3 months of initial surgery. Of these 8 patients, 6 patients underwent ileostomy closure without any anastomotic stricture related problem. One patient endured anastomotic stricture but that was managed by pre and post reversal dilation. Another patient sought ileostomy reversal surgery after 6 months of initial surgery, but ileostomy reversal was not attempted due to the development of severe anastomotic stricture. Conclusion: This study statistically cannot conclude that, early closure gives a better outcome. However, the chance of developing anastomotic strictures (benign) is more, if the site of anastomosis left nonfunctional for long. Journal of Surgical Sciences (2023) Vol. 27 (1) : 6-10